The Influence of Loving Local Culture on the Student Profile of Pancasila Global Diversity Elements - Juanta, Palma; Salsabilla, Aischa Najwa; Sianturi, Authon Siloam; Zendrato, Beatrice Samala; Alfadilla, Rayyan; Abdillah, Satria; Putri, Yulia Anjani (Universitas Negeri Medan, 2024)
Technological advances that continue to advance have made many changes for the world community, especially Indonesia. Indonesia has many cultural varieties such as ethnicity, religion, race, language and culture that must be maintained, especially among young people as the generation that will become future leaders. The application of the Pancasila student profile, an element of global diversity, is one of the things that needs to be done to maintain and care for local culture so that it is not left behind by technological advances. This research aims to find out how important it is for students to instill an attitude of loving local culture towards the student profile of Pancasila, an element of global diversity. This study uses quantitative descriptive to obtain research data results using numbers. This research was conducted at SMA Negeri 15 Medan in March-June 2024. The population in this study is class X students. and the sample of this study is class X-7 which totals 36 students. Data collection in this study uses a research instrument that uses a survey method in the form of a questionnaire. The data analysis techniques in this study are data collection, statistical tests, data presentation and conclusion drawn.